ANALISIS KADAR ARSEN (As) PADA AIR SUMUR PETANI DI DESA SUMBER SARI KECAMATAN LOA KULU KUTAI KARTANEGARA - Siringoringo, Agnes Sri Yunyartia; Eka Farpina; Ganea Qorry Aina (LPPM STIKes Mitra Adiguna, 2024)
Well water is one of the important needs in agriculture. Where well water can contain heavy metal arsenic in it. The content of the heavy metal arsenic if consumed continuously can be fatal to health. The purpose of this study was to determine arsenic levels in farmer's well water in Sumber Sari Kulu Village, Kutai Kartanegara. The type of research used is descriptive research. The samples in this study were 10 wells in Sumber Sari Village, Kutai Kartanegara, with a total sample of 500 ml. The sampling technique used is total sampling. The variable in this study was the content of the heavy metal arsenic with the data analysis using univariate analysis. Based on the research results, the arsenic levels in samples 1 and 3 were 0.0020 mg/L and 0.0080 mg/L while the other 8 samples did not contain arsenic (0 mg/L). Based on Minister of Health Regulation No. 32 of 2017 well water that meets quality standards is 100%.